Effect of inactive Rabies virus vaccine in spleen structure of species Myotis myotis - إبراهيم, نهلة (Latakia University Journal -Biological Sciences Series, 2024)
In this research, we identified the morphology and histological structure of the spleen at Myotis myotis (family Vespertilionidae) and studying of changes in the structure of the spleen as a result of response to inactive rabies vaccine, We used adult animals randomly: inactive virus with a main dose and two supportive doses in the third and tenth days, We compared the structure of the species' spleens before and after the doses. The morphological study of the spleen showed that it appears pink in colour and has a flat, elongated and curved shape, swollen at one end. Histologically, the spleen tissue generally consists of two distinct regions, the red pulp, the white pulp and a Marginal Zones are the boundary zone between the red pulp and white pulp, and it is surrounded by thin capsule that forms the outer covering. On day 10 during the tenth day after dosing the species with inactive rabies vaccine, lymphatic hyperplasia, splenomegaly, global vacuolar necrosis of liver cells, and the appearance of storage foci occur.